208k views
0 votes
Pls help me with this questions​

Pls help me with this questions​-example-1

1 Answer

3 votes

Explanation:

6a

Sn = n/2 [2a + (n-1) d]

(2Sn)/ n = 2a + (n - 1) d

2a + (n-1) d = (2Sn)/n

(n-1) d = (2Sn - 2a)/n


d = (2sn \: - 2a)/((n(n - 1)))


d = \frac{2(sn - a)}{ {n}^(2) - n}

6b


d = \frac{2(56 - 25)}{ {32}^(2) - 32}

d = ¹/16

7a.

E = (mv²)/2 + mgh

E = m( v²/2 + gh)

E/m = v²/2 + gh

E/m - gh = v²/2

2(E/m - gh) = v²

so


v = \sqrt{2( (e)/(m) - gh)}

7b.


v = \sqrt{2( (4900)/(20) - 9.8 * 15)}

v = 14 m/s

User Sudheer KB
by
5.1k points